How to Integrate Nanotechnology into Chemical Engineering Education: A Bibliometric and Technological Review of Curriculum Standards, Research Trends, Pedagogical Challenges, and Future Prospects - Asep Bayu Dani Nandiyanto; Teguh Kurniawan; Muhammad Roil Bilad; Abdulkareem Sh. Mahdi Al-Obaidi; Obie Farobie; Belkheir Hammouti (ASEAN Journal of Educational Research and Technology, 2026)
This study examines the integration of nanotechnology into chemical engineering education and its implications for future curriculum development. A bibliometric and technological review was conducted using publications from major scientific databases, with standardized datasets and mapped collaboration and keyword networks to identify pedagogical and curricular trends. The findings indicate a steady growth of interdisciplinary research linking nanoscale concepts with process engineering, accompanied by increasing adoption of virtual laboratories, computer simulations, and intelligent tutoring systems. Nevertheless, challenges remain, including uneven faculty preparedness, limited access to advanced instrumentation, and the lack of unified competency frameworks across institutions. These constraints are largely driven by macro-centric teaching traditions, resource limitations, and inconsistent curriculum standards. To address these gaps, the study proposes targeted updates to core and elective courses that emphasize nano-centric content, sustainability, and digital pedagogy. Overall, the paper presents a practical framework aligned with Safe-by-Design principles and the United Nations Sustainable Development Goals.